Peran Aplikasi Seluler terhadap Peningkatan Informasi Imunisasi Anak Bagi Orang Tua: Studi Literatur - Astuti Astuti; La Ode Abdul Rahman (Jurnal Keperawatan, 2020)
Immunization is important for children because it can prevent various infectious diseases thatcan inhibit a child's growth and development. The provision of immunization in children isoften found various obstacles caused by the target of immunization cannot be achieved. Thiscan be caused due to a lack of information and immunization schedule errors due to the manytypes of immunizations with different schedules. As technology develops, various health-relatedcellular applications emerge called mhealth. Mhealth related to immunization is expected toincrease information for parents so they can provide immunizations for their children asrecommended. The purpose of this study is to determine the role of mobile applications relatedto immunization in increasing immunization information for parents. Literature is collected forreview, literature search uses several online databases that are included in the inclusioncriteria and is limited to 2015-2020. Nine articles are used as the main analysis, other articlesare added to support the discussion. Cellular applications related to immunization areavailable in various forms. Overall, these applications have a major role in providinginformation about immunization knowledge and immunization schedule information to increaseparental participation to provide immunizations to their children in full. Therefore, healthworkers, especially those directly related to child immunization, are advised to encourage theuse of mobile applications related to immunization against parents in order to achieve goalsrelated to immunization in children.